Analisis Kinerja Simpang Tiga Bersinyal dengan Simulasi PTV Vissim di Koridor Jalan (Studi Kasus: Jalan Jenderal Ahmad Yani Utara – Jalan Raden Intan, Kota Malang) - Yakobus Ronaldo Arianto; Erizaldy Azwar; Raymond Valiant; Ari Murdhianti (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
Traffic flow at the intersection with traffic lights on Jalan Jend. Ahmad Yani Utara-Jalan Raden Intan, Blimbing, Malang, is often disrupted due to significant congestion and traffic delays. This study aims to evaluate the performance of the intersection and examine the traffic light operation model using PTV Vissim microscopic simulation software. The data collected included primary and secondary data. Primary data included vehicle volume, physical characteristics of the intersection, queue length, vehicle speed, and traffic light cycle. Secondary data was obtained from digital maps and documents related to road capacity. The research method used was quantitative descriptive with a simulation approach. The analysis was conducted based on a traffic flow of 3,877 pcu/hour, a saturation level of 3.57, an average queue length of 335.76 meters, a traffic delay of 54.95 seconds per vehicle, and an average vehicle speed of less than 36.7 km/hour. Furthermore, driver behavior parameter calibration was performed to ensure the accuracy of the model. With a GEH value of less than five, the PTV Vissim model proved to be valid and capable of accurately describing real traffic conditions. The results of this study indicate that simulation models can be used to design and evaluate traffic light control strategies, thereby improving vehicle flow and reducing queues and delays at the intersection. Next, driver behavior parameters were calibrated to ensure the accuracy of the model. With a GEH value of less than five, the PTV Vissim model proved to be valid and capable of accurately describing real traffic conditions. The results of this study indicate that simulation models can be used to design and evaluate traffic light control strategies, thereby improving traffic flow and reducing queues and delays at intersections. These findings can also serve as a basis for decision-making related to traffic management in the urban area of Malang.